2005
DOI: 10.1159/000086314
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Genetically Modified Crops to Minimize the Risk of Increased Food Allergy: A Review

Abstract: The first genetically modified (GM) crops approved for food use (tomato and soybean) were evaluated for safety by the United States Food and Drug Administration prior to commercial production. Among other factors, those products and all additional GM crops that have been grown commercially have been evaluated for potential increases in allergenic properties using methods that are consistent with the current understanding of food allergens and knowledge regarding the prediction of allergenic activity. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 200 publications
1
64
0
1
Order By: Relevance
“…Although it may seem outdated to classify organisms capable of inducing allergic reactions rather than their molecular structures, the still expanding knowledge on allergenic sources is a continuous challenge for achieving the most comprehensive list of allergen molecules. It is also important to keep in mind that the emergence of allergy as a problem in developing countries and the globalization in terms of mobility of people and goods create new allergenic sources [23,24,25] and new routes of exposure [26]. Thus, a reliable database resource for allergenic organisms should be established as well.…”
Section: Allergen Lists Sequence Databases and Computational Toolsmentioning
confidence: 99%
“…Although it may seem outdated to classify organisms capable of inducing allergic reactions rather than their molecular structures, the still expanding knowledge on allergenic sources is a continuous challenge for achieving the most comprehensive list of allergen molecules. It is also important to keep in mind that the emergence of allergy as a problem in developing countries and the globalization in terms of mobility of people and goods create new allergenic sources [23,24,25] and new routes of exposure [26]. Thus, a reliable database resource for allergenic organisms should be established as well.…”
Section: Allergen Lists Sequence Databases and Computational Toolsmentioning
confidence: 99%
“…Another harmful effect is the occurrence of antibiotic-resistant infections as a result of transference of genes to pathogenic micro-organisms when marker genes used in gene transference are used together with original gene. Moreover, it has been shown that foreign DNAs used as food can be transferred to cells and thus may cause genetic defects human DNA [12]. In addition to these, there are studies showing that GM foods would decrease biological diversity in the future years [10,13].…”
Section: Introductionmentioning
confidence: 99%
“…Regulatory bodies in various countries differ in their requirements for evaluating the safety or potential risks of products that include these newly introduced proteins. The US, EU, and many other countries have now implemented requirements for evaluating the potential allergenicity of such products [1]. The primary focus, either elaborated or implied, is on preventing the transfer of a known allergen, or a protein sufficiently similar to a known allergen that it may trigger allergic crossreactions.…”
Section: Introductionmentioning
confidence: 99%